The Digital Notary: Harnessing Artificial Intelligence in the Transition to Society 5.0 - Ahmad Muhajir Firrizqi Mubaroq; Auliya Safira Putri (Rechtenstudent, 2025)
The rapid development of digital technology has propelled humanity from the era of the Industrial Revolution 4.0 into Society 5.0, which adopts a human-focused approach aiming for a synergy between technology, humanity, and data. The sophistication of technology has led to the creation of artificial intelligence (AI), which is designed to enable computer systems to simulate several functions of the human brain. The utilization of AI has been adopted across various professional sectors, including the legal profession. Notaries, as public officials authorized to draw up authentic deeds, perform their duties in accordance with the Notary Position Act. This statutory obligation, which requires a physical meeting for the execution of authentic deeds, has hindered notaries from fully utilizing digital media in the process of deed-making. Therefore, this study aims to analyze the development of AI as a catalyst for the emergence of Digital Notaries in the future. The result of this analysis indicates that the development of Digital Notaries utilizing AI can be realized through legal reforms that offer both preventive and repressive legal protections, as well as through the readiness and creativity of notaries to compete globally in the digital realm.